Interventions to develop an improvement culture within nonprofit organization: The case of Saudi Arabia - Almaiman, Sulaiman; McLaughlin, Patrick; Al-Ashaab, Ahmed (Cranfield University, 2017)
It has been confirmed that organizational culture has a remarkable impact on facilitating continuous improvement. Nonetheless, little empirical research has investigated how organizational culture can facilitate continuous improvement. Therefore, this paper asks what interventions facilitate a continuous improvement culture within nonprofit organizations. Qualitative data are suggested as an appropriate method for answering the research question. The present research adopted an interpretive paradigm whereby reality, treated as a subjective and multiple entity that is “socially constructed”, can be mentally explored from the participants' perspectives. Grounded theory was the chosen approach for collecting and analysing the qualitative data; thus, the constructed theories were ‘grounded’ in the data themselves. Thirty one interviews in fifteen nonprofit organizations yielded data which, when analysed revealed a number of interventions, developed by the participants during five focus group discussions.
Keywords: Organizational culture; Continuous improvement; Nonprofit organizations